Behavioral and neuroimaging research on Developmental Coordination Disorder (DCD): a combined systematic review and meta-analysis of recent findings - Subara-Zukic, Emily; Cole, Michael H.; McGuckian, Thomas B.; Steenbergen, Bert; Green, Dido; Smits-Engelsman, Bouwien CM; Lust, Jessica M.; Abdollahipour, Reza; Domellöf, Erik; Deconinck, Frederik J. A.; Blank, Rainer; Wilson, Peter H. (Frontiers in psychology, 2022)
AimThe neurocognitive basis of Developmental Coordination Disorder (DCD; or motor clumsiness) remains an issue of continued debate. This combined systematic review and meta-analysis provides a synthesis of recent experimental studies on the motor control, cognitive, and neural underpinnings of DCD.MethodsThe review included all published work conducted since September 2016 and up to April 2021. One-hundred papers with a DCD-Control comparison were included, with 1,374 effect sizes entered into a multi-level meta-analysis.ResultsThe most profound deficits were shown in: voluntary gaze control during movement; cognitive-motor integration; practice-/context-dependent motor learning; internal modeling; more variable movement kinematics/kinetics; larger safety margins when locomoting, and atypical neural structure and function across sensori-motor and prefrontal regions.InterpretationTaken together, these results on DCD suggest fundamental deficits in visual-motor mapping and cognitive-motor integration, and abnormal maturation of motor networks, but also areas of pragmatic compensation for motor control deficits. Implications for current theory, future research, and evidence-based practice are discussed.Systematic Review RegistrationPROSPERO, identifier: CRD42020185444.
Gesehen am 22.03.2022